The effect of various stocking densities on growth performance of Arabian yellowfin seabream (Acanthopagrus arabicus) cultivated in cages at Basrah province - Hussein, Sadek A.; Al-Faiz, Nawras A.; Yesser, Abdul- Karim T. (Iraqi Journal of Aquaculture, 2021)
The effect of various stocking densities (20, 30, 40 fish/m3) on the final weight, weight gain, specific growth and daily growth rates in Arabian yellowfin seabream (Acanthopagrus arabicus) reared in floating cages (2m3) was studied. The trials were performed in Faw district Southern Basrah. Results indicate that stocking at 20 fish/m3 provide significant (P<0.05) final weight compared to individuals cultivated at a density 30 and 40 fish/m3, while the final weights of fish reared at a density of 30 and 40 fish/m3 didn't differ significantly (P>0.05), the highest final weight (55.58±5.84g) attained at density 20 fish/m3, 52.13 ± 6.12 at 30 fish/m3 and (50.51± 6.98) at stocking density 40 fish/m3. Statistically analysis showed that weight gain and daily growth were significant differs (P<0.05) among treatments. Specific growth rates and survival rates reveal no differences significantly (P>0.05) depending on the stocking densities 20, 30 and 40 fish/m3.